Ligation-free ribosome profiling of cell type-specific translation in the brain. Issue 1 (December 2016) - Hornstein, Nicholas; Torres, Daniela; Das Sharma, Sohani; Tang, Guomei; Canoll, Peter; Sims, Peter
Abstract Ribosome profiling has emerged as a powerful tool for genome-wide measurements of translation, but library construction requires multiple ligation steps and remains cumbersome relative to more conventional deep-sequencing experiments. We report a new, ligation-free approach to ribosome profiling that does not require ligation. Library construction for ligation-free ribosome profiling can be completed in one day with as little as 1 ng of purified RNA footprints. We apply ligation-free ribosome profiling to mouse brain tissue to identify new patterns of cell type-specific translation and test its ability to identify translational targets of mTOR signaling in the brain.